2013
DOI: 10.1186/1475-2840-12-76
|View full text |Cite
|
Sign up to set email alerts
|

Neck circumference as an independent predictive contributor to cardio-metabolic syndrome

Abstract: BackgroundThe predictive potentials of neck circumference (NC) for cardio-metabolic risks remain uncertain. The aim of this study was to investigate whether NC independently contributes to the prediction of cardio-metabolic risks beyond body mass index (BMI), waist circumference (WC) and waist to hip ratio (WHpR) in a large Chinese population.MethodsA total of 4201 participants (2508 men and 1693 women) aged 20-85 were recruited from the Health Examination Centre between May 2009 and April 2010, anthropometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
149
2
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(180 citation statements)
references
References 28 publications
(42 reference statements)
17
149
2
12
Order By: Relevance
“…Another study explains that individuals with abnormal NCwill have a risk of elevated levels of triglycerides that can lead to metabolic syndrome and cardiovascular disease [16], [17].…”
Section: Resultsmentioning
confidence: 99%
“…Another study explains that individuals with abnormal NCwill have a risk of elevated levels of triglycerides that can lead to metabolic syndrome and cardiovascular disease [16], [17].…”
Section: Resultsmentioning
confidence: 99%
“…In the former studies, the correlation between obesity and metabolic disorders and cardiovascular risk factors has been established (11). Even though BMI, WC and W/H ratio are anthropometric indexes commonly used in the diagnosis of obesity, the number of publications stating that NC is an easier and faster parameter has been gradually increasing during recent years (9).…”
Section: Discussionmentioning
confidence: 99%
“…In community-based studies, it has been demonstrated that there is a positive correlation between NC and metabolic risk factors, insulin resistance and visceral adipose tissue, and that it is an independent determinant for the cardiometabolic syndrome (10,11). In addition, the correlation between central obesity and NC has also been demonstrated in different ethnic groups, diabetics and children (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…NC is an anthropometric measure of obesity which reflects fat deposition in the upper body. Association of NC with MS and its components, insulin resistance, fatty liver disease, sleep apnea and biomarkers of inflammation have been previously reported [2][3][4][5][6][7][8][9][10][11]. Interestingly, new studies have demonstrated an association between NC and indicators of atherosclerosis, as carotid intimalmedia thickness, but not coronary artery calcium [12].…”
Section: Commentarymentioning
confidence: 99%